Synthesis and characterization of 1,2,4-triazolo-1,3,4-thiadiazoles - Loo, Xin Tong (2022)
In this project, a 1,2,4-triazole and eight 1,2,4-triazolo-1,3,4-thiadiazole derivatives have been successfully synthesized and characterized. On the other hand, 1,2,4-triazolo-1,3,4-thiadiazoles were synthesized through refluxing 1,2,4-triazole and benzoic acid derivatives in the presence of phosphorous oxychloride as the cyclization agent. The 1,2,4-triazolo-1,3,4-thiadiazole derivatives were named as XT1, XT2, XT3, XT4, XT5, XT6, XT7 and XT8 for different substituents which were H, 4-Cl, 2-Cl, 2,4-Cl2, 3-CF3, 4-CF3, 4-OCH3 and 4-NO2, respectively. The structure of 1,2,4-triazole and 1,2,4-triazolo-1,3,4-thiadiazole derivatives (XT1-XT8) were characterized by FT-IR, 1H NMR, 13C NMR, DEPT, HMQC and HMBC spectroscopies as well as melting point apparatus. The percentage yield of 1,2,4-triazole obtained was 31 % whereas XT1-XT8 were synthesized with the percentage yield in the range of 8 – 69 %.